MoS2@C with S vacancies vertically anchored on V2C-MXene for efficient lithium and sodium storage. Issue 5 (6th February 2023) - Liu, Guilong; Zhang, Ting; Li, Xiaojie; Li, Jin; Wu, Naiteng; Cao, Ang; Yuan, Weiwei; Pan, Kunming; Guo, Donglei; Liu, Xianming
Abstract : V2 C-MXene induced abundant S vacancies and modulated the charge distribution of MoS2, thereby enhancing the intrinsic conductivity and providing more active sites for ion adsorption. V2 C-MoS2 @C displayed excellent electrochemical performance in LIBs and SIBs. Abstract : Molybdenum sulfide (MoS2 ) with a high theoretical capacity and large interlayer distance has triggered extensive attention as a promising alternative anode for lithium ion batteries (LIBs) and sodium ion batteries (SIBs). However, the sluggish kinetics and structural collapse induced by its poor conductivity usually lead to unsatisfactory rate capability and poor cycling performance. Herein, few-layered MoS2 with abundant S vacancies were anchored on V2 C-MXene and embedded in carbon via an in situ assembly and carbonization strategy. The V2 C-MXene substrate suppressed the agglomeration and stacking of MoS2 nanosheets, facilitated the efficient exposure of MoS2 and shortened the diffusion pathways, which favored ion accessibility and induced a strong capacitive-controlled charge storage behavior. Experimental results and theoretical calculations revealed that the electronic coupling between MoS2 and V2 C-MXene not only induced abundant S vacancies and modulated the charge distribution but also promoted Li/Na adsorption and lowered the ion diffusion energy barrier. Consequently, the V2 C-MXene coupled MoS2 @C electrode delivered high capacities of 732.8 and 337.3 mA h g −1 at 1 A g −1 in LIBs and SIBs, respectively. This work provided a new insight into the rational design of stable and advanced electrode materials for energy storage and conversion.